Optical properties of functionalized nanodiamonds. Issue 1 (December 2017) - Pichot, V.; Muller, O.; Seve, A.; Yvon, A.; Merlat, L.; Spitzer, D.
Abstract Detonation nanodiamonds exhibit strong nonlinear optical properties depending on their electronic properties. In the present paper, the nanodiamond functional groups are chemically modified to obtain nanodiamonds with primary amines on their surface. The optical properties of such nanodiamonds placed in water suspensions are studied and compared with the one of classical detonation nanodiamonds. Transmission, scattering and Z-scan experiments are performed for two different wavelengths (532 nm and 1064 nm). A lower threshold for optical limiting associated to more pronounce non-linear optical effects is detected at the wavelength of 1064 nm compared to the one at 532 nm. This effect may be due to a stronger nonlinear backscattering behavior at 1064 nm. Moreover, a striking result obtained from the Z-scan experiments reveals a completely different behavior of the functionalized nanodiamonds for both wavelengths. This result is discussed in regard to the electronic properties of the material and possible charge transfer.